Mini-k'iwh'e:n (For That Purpose—I Consider Things): (Re)writing and (Re)righting Indigenous Menstrual Practices to Intervene on Contemporary Menstrual Discourse and the Politics of Taboo. (February 2017) - Risling Baldy, Cutcha
Historically, studies of Indigenous menstrual practices were mired in assumptions that these practices were oppressive toward women. The high regard for menstruation as demonstrated through Indigenous women's coming of age ceremonies and the continuing rituals of menstruation among Indigenous peoples has not been critically engaged with, and is often relegated to dismissive and oversimplified statements. The Western menstrual taboo not only influences theories of Indigenous menstrual customs but also relies on settler colonial rhetoric to help support a continuing politics of taboo. Although there have been numerous cultural studies of modern menstrual discourse focused on how contemporary Western menstrual practices are rooted in patriarchal bias, even self-declared feminist literature treats the menstrual taboo as nearly universal to Indigenous menstrual practices. This article provides an Indigenous feminist critique of contemporary menstrual discourse. I begin with a short history of settler colonialism and menstrual discourse and then analyze contemporary popular menstrual discourse. The final part of this article is an intervention on the assumed Indigenous menstrual taboo by looking at menstrual practices of the Hoopa Valley Tribe, located in Northern California, to demonstrate that for this culture and society, there is no menstrual taboo. It is through this in-depth analysis of Hupa menstrual practices that we see how Indigenous feminisms challenge settler colonialism and provide a decolonizing lens to contemporary scholarship that not only imagines alternative analyses but also acknowledges that these alternatives did, have always, and will always exist.